Mining microcapsule self-repairing hole sealing material and preparation method thereof
By using a micro -capsule sealing material prepared by the use of silate -based nano -fibrin -modified crisadaldehyde resin and bisphenol S type epoxy resin, the early intensive strength of the coal mine sealing pore material is low, easy to shrink and lack of self -repair function. Realize the automatic repair and long life of materials.
Patent Information
- Application Number
- CN202411494982.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coal mine sealing materials have problems such as low strength, high cost, easy shrinkage and cracks, and lack of rapid self-repair function, which leads to failure of drilling seals and affects coal mine production safety and miners' health.
A microcapsule sealing material prepared by silanized nanocellulose modified urea-formaldehyde resin as the capsule wall material and bisphenol S-type epoxy resin as the core material is used. Through the curing reaction of the spherical structure of the microcapsule and the core repair agent , to achieve automatic repair of fine cracks inside the material.
The efficient self -repair function of the material is realized, the service life of the sealing materials is extended, the maintenance cost of the holes is reduced, and it has good high temperature resistance and chemical stability.
Smart Images

Figure CN119349921A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal mine sealing, and in particular relates to a mine-used microcapsule self-repairing sealing material and a preparation method thereof. Background Art
[0002] Coal is my country's basic energy and important industrial raw material. Coal safety production is the key to protecting the lives and health of miners and promoting the sustainable development of the coal industry. However, in the process of coal seam gas extraction, hydraulic measures for disaster prevention, and plugging of cracks, drilling material failure will occur. The nature of the sealing material determines the quality of the drilling seal, which in turn affects the efficiency of gas extraction and water injection, as well as the plugging of coal seam cracks and the filling of surrounding rock cracks.
[0003] At present, the widely used coal mine sealing materials are mainly divided into four categories: clay (yellow mud) materials, polymer materials, high-water quick-setting solid materials (high-water materials) and cement-based materials. The advantages of clay (yellow mud) materials are low cost and strong availability, but they are very sticky and easily form cavities between them and the inner wall of the borehole, causing air leakage in the hole. They are currently on the verge of being eliminated. The main polymer materials are polyurethane expansion materials, which are easy to construct, have a large expansion rate, and can seal holes quickly, but they have problems such as low compressive strength, high cost, toxicity, and easy shrinkage after solidification. High-water material is a solid material that can quickly solidify and solidify, and has the advantages of strong impermeability, short curing time, and good fluidity. The disadvantages are that the filling material is not strong enough, the cost is high, and the service life is short. The "two blocking and one injection" pressure grouting sealing method is a drilling sealing process widely used in coal mines. Among them, cement-based materials are the most commonly used grouting sealing materials, but their early strength is not high, they will shrink and crack after solidification, and it is not easy to seal fine cracks after drying, so that the outside air enters the borehole from the internal pores under the action of the negative pressure of extraction, forming an air leakage channel, which affects the quality of sealing the borehole.
[0004] Chinese patent CN113636789A discloses "Coal mine underground gas extraction sealing material and preparation method thereof", which has good water retention and water absorption, and can form a dense combination with the borehole wall to seal the cracks after the initial sealing. However, long-term extraction will cause gas leakage in the coal body around the borehole and regeneration of cracks in the blocked surrounding rock. Chinese patent CN111911111A discloses "A gas extraction sealing material and its use method", which uses bentonite, diatomaceous earth-immobilized microorganisms, microbial nutrient solution and other components as raw materials, reducing the use of polymer materials, and microorganisms will repair a large number of micropores, with good sealing effect and high stability. However, this material relies on the biological activity of Bacillus pasteurianus, is not suitable for coal seams with high water content, and the microbial reaction cycle is long, and the repair process can only be started after the crack position is located.
[0006] Existing sealing materials generally have defects such as low early strength, high cost, easy shrinkage and cracking, and harm to human health. They are not suitable for the high temperature and high humidity working environment of coal mines, and usually do not have rapid self-repair functions. Once cracks appear again in the sealing material body, the gap between the sealing material and the extraction pipeline, and the grouting around the borehole, it is impossible to repair the fine cracks and internal cracks at specific locations, causing the borehole seal to fail, which seriously threatens the safe production of coal mines and the physical and mental health of miners. Therefore, it is particularly necessary and urgent to provide a sealing material with low cost, good comprehensive performance, excellent sealing, and the ability to automatically repair fine cracks. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of existing sealing materials such as easy shrinkage during solidification, low strength, and difficulty in repairing fine cracks at specific locations, and to provide a self-repairing microcapsule sealing material for mining and a preparation method. The microcapsule sealing material prepared by the present invention has relatively low cost, simple operation, good high temperature and high pressure resistance, and can adapt to the harsh environment deep in the coal seam. The microcapsules can automatically repair fine cracks inside the material and extend the service life of the sealing material.
[0008] The scheme of the present invention is achieved by:
[0009] The mining microcapsule self-repairing sealing material consists of a wall material and a core material. The wall material covers the core material, and the wall material gradually becomes dense and finally covers the microcapsule. In terms of weight, the capsule wall is 15 to 18 parts of modified urea-formaldehyde resin of silylated nanocellulose, and the capsule core is 2 to 4 parts of bisphenol S epoxy resin diluted with an active diluent.
[0010] The preparation method of the present invention comprises the following steps:
[0011] (1) dissolving the reactive monomer urea of the capsule wall material in a formaldehyde (37% to 40%) aqueous solution, stirring under constant temperature magnetic force for 0.5 to 1 h at room temperature, and preparing a solution with ethanol and deionized water in a volume ratio of 3:1, adding hexadecyltrimethoxysilane and nanocellulose, and then transferring the mixed solution into a 250 ml three-necked flask, adjusting the temperature of a constant temperature water bath to 75° C., and continuously stirring to obtain a viscous and transparent prepolymer aqueous solution;
[0012] (2) adding urea-formaldehyde resin prepolymer, compound emulsifier, bisphenol S epoxy resin and its active diluent into a 500 ml four-necked flask, adding a pH adjuster to make the mixed solution neutral, stirring it evenly with a glass rod, adding 1 to 2 drops of n-octanol as a defoaming agent, reacting in a constant temperature water bath at 60° C., with a rotation speed of 500 to 800 rpm, to obtain a stable oil-in-water (O / W) emulsion;
[0013] (3) placing the mixed emulsion in step (2) in a water bath, adding a certain amount of ammonium chloride to the flask in portions, slowly adjusting the pH value of the solution to 3-4, and reacting for 1-2 hours at a certain temperature and stirring speed. At this time, the environment is acidic, and urea-formaldehyde resin particles gradually deposit on the surface of the epoxy resin droplets to form the capsule wall of the microcapsule;
[0014] (4) adding an appropriate amount of curing agent to the acidified microcapsule solution, and slowly raising the temperature to 80° C. to cure the microcapsules for a period of time. When the temperature drops to room temperature, washing the reaction product 3 to 4 times with a 30% ethanol solution, and then filtering it under reduced pressure with a Buchner funnel. After filtering, drying, placing it in an electric constant temperature forced air drying oven at 65° C. for 24 hours, thereby obtaining urea-formaldehyde resin-epoxy resin microcapsules;
[0015] (5) A 1% acetic acid solution is prepared as a hydrolysis catalyst, a silane coupling agent is dropped into the acetic acid solution, and the mixture is stirred rapidly to prevent the formation of gel, an appropriate amount of microcapsule powder is added to the silane coupling agent aqueous solution, and the mixture is reacted at a constant temperature of 30 to 40° C. for 1 hour, and the microcapsules are taken out and washed with deionized water for 3 to 4 times, and then filtered and dried to obtain a microcapsule sealing material sample whose surface is covered with a silane coupling agent; further, the synthesized microcapsules are incorporated into a cement-based material to obtain a self-repairing microcapsule cement-based sealing material.
[0016] Furthermore, in step (1), the molar ratio of urea to formaldehyde solution is 1:1-2.
[0017] Furthermore, in step (1), the mass ratio of hexadecyltrimethoxysilane to nanocellulose is 3:1.
[0018] Furthermore, in step (1), the stirring speed of the constant temperature water bath is 300 to 500 rpm.
[0019] Furthermore, in step (2), the mass ratio of urea-formaldehyde resin prepolymer to epoxy resin is 1.2:1.
[0020] Furthermore, in step (2), the active diluent is 1,4-butanediol diglycidyl ether, and the amount of the active diluent is 10% to 20% of the epoxy resin.
[0021] Furthermore, in step (2), the compound emulsifier is sodium dodecylbenzene sulfonate (LAS) and fatty alcohol polyoxyethylene ether (AEO-9), and the compounding ratio is 1:1, that is, the mass ratio of the two emulsifiers is 1:1.
[0022] Furthermore, in step (2), the pH regulator is a dilute hydrochloric acid solution with a concentration of 2% to 4%.
[0023] Furthermore, in step (3), the stirring temperature is 60-70° C., and the stirring speed is 400-500 rpm.
[0024] Furthermore, in step (4), the curing agent is a fatty amine curing agent triethylenetetramine, and the curing time is 2 hours.
[0025] Furthermore, in step (5), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, namely KH-570 silane coupling agent; and the mass ratio of the silane coupling agent aqueous solution to the urea-formaldehyde resin-epoxy resin microcapsules is 1:25.
[0026] Furthermore, in step (5), the drying temperature is 55° C. to 65° C., and the drying time is 2 to 3 hours.
[0027] Furthermore, in step (5), the amount of microcapsules added is 3% to 4% of the cement content.
[0028] The self-repairing microcapsule cement-based sealing material of the present invention can be used for sealing operations of various types of drilling holes such as coal seam water injection drilling holes and fracturing drilling holes, and for plugging coal seam cracks and holes, and has wide applicability.
[0029] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0030] (1) The spherical structure of the microcapsules in the material of the present invention can contact the microcracks in all directions, and the active repair process can be realized without detecting the exact location of the cracks, and the reaction rate is generally fast. Once the cement-based material is damaged or cracks are generated again at the grouting area around the drill hole, the microcapsules rupture to release the capsule core repair agent, which participates in the curing reaction to seal the microcracks, thereby extending the service life of the material and reducing the cost of sealing and repair.
[0031] (2) The synthesis and blending process of the urea-formaldehyde resin-epoxy resin microcapsules in the present invention are simple, low-cost, and have good mechanical properties and chemical stability; the introduction of silylated nanocellulose improves the water resistance and corrosion resistance of the urea-formaldehyde resin, reduces the content of free formaldehyde, and the resin after the curing reaction is non-toxic, pollution-free, and has excellent wear resistance; the gelation and curing speed of bisphenol S type epoxy resin is fast, and the addition of a diluent can reduce its viscosity, which helps to penetrate into cracks and pores to achieve more thorough filling and repair; the silane coupling agent used in the material of the present invention can effectively improve the bonding strength between the microcapsules and the substrate and improve the interface compatibility.
[0032] (3) The microcapsule self-repairing sealing material prepared by the present invention has good thermal stability, can be used for a long time in high temperature and harsh environment underground, will not deform or soften at room temperature, and has good environmental adaptability and durability. At the same time, it has good pressure resistance and mechanical properties, has high hardness and strength, can withstand the high pressure generated during the fracturing process of liquid CO2, and meets the mechanical requirements of drilling and sealing. All components of the material are derived from commercially available materials, and the operation is simple and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a process flow chart for synthesizing the self-repairing microcapsule cement-based sealing material. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0035] The self-repairing sealing material of the mining microcapsule comprises, by weight, 16 parts of modified urea-formaldehyde resin of silanized nanocellulose as the capsule wall and 3 parts of bisphenol S epoxy resin diluted by an active diluent as the capsule core.
[0036] The preparation method of the mining microcapsule self-repairing sealing material comprises the following steps:
[0037] (1) 8 g of urea and 21 g of a 37% formaldehyde solution were poured into a beaker and mixed, and the mixture was stirred under a constant temperature magnetic force at room temperature for 1 h. Ethanol and deionized water were prepared into a solution in a volume ratio of 3:1, 7.56 g of hexadecyltrimethoxysilane and 2.52 g of nanocellulose were added thereto, and the mixture was transferred into a 250 ml three-necked flask, and stirred continuously at 400 rpm in a constant temperature water bath at 75°C to obtain a viscous and transparent prepolymer aqueous solution;
[0038] (2) Prepare an aqueous solution of an emulsifier with a mass fraction of 0.5%, adjust the pH to 7 with 2% dilute hydrochloric acid, pour in 10 g of bisphenol S epoxy resin, add 10% of 1,4-butanediol diglycidyl ether and mix and stir, add urea-formaldehyde resin prepolymer and the pre-prepared mixed solution into a 500 ml four-necked flask, add 1 to 2 drops of n-octanol as a defoamer, stir at a constant temperature of 60° C. for 40 min, and control the rotation speed to 500 rpm to obtain a stable oil-in-water (O / W) emulsion;
[0039] (3) placing the mixed emulsion in step (2) in a water bath, adding 0.5 g of ammonium chloride to the flask, slowly adjusting the pH value of the solution to 3, heating to 65° C. and reacting for 1.5 h at a stirring speed of 450 rpm. Under this acidic condition, urea-formaldehyde resin particles gradually deposit on the surface of the epoxy resin droplets to form the capsule wall of the microcapsule;
[0040] (4) Add 0.5 g of curing agent triethylenetetramine to the acidified solution, heat the water bath to 80° C. for reaction for 2 h, cool naturally to room temperature, wash the obtained product 3 to 4 times with 30% ethanol solution, and then filter it under reduced pressure with a Buchner funnel. After filtering, place it in an electric constant temperature blast drying oven at 65° C. for drying for 24 h to obtain urea-formaldehyde resin-epoxy resin microcapsules;
[0041] (5) Prepare 1% acetic acid solution as a hydrolysis catalyst, add 0.8g of silane coupling agent KH-570, and stir rapidly to prevent gel formation, add microcapsule powder to the silane coupling agent aqueous solution, continue to react at a constant temperature of 40°C for 1h, then take out the microcapsules and wash them with deionized water for 3 to 4 times, filter, and dry in a drying oven at 60°C for 2h to obtain a microcapsule sealing material sample with a silane coupling agent on the surface; further, add 3% of microcapsules to the cement-based material to obtain a self-repairing microcapsule cement-based sealing material.
[0042] The microcapsule sealing material prepared above has efficient self-repairing function and good mechanical properties, and can be used in coalbed methane mining and other fracture pore sealing processes, while also being able to improve the efficiency and stability of liquid CO2 fracturing technology.
[0043] It can be understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A self-repairing sealing material for mining and a preparation method thereof, characterized in that: The microcapsule sealing material is composed of a wall material and a core material, wherein the wall material covers the core material, and the wall material gradually becomes dense and finally covers the microcapsule; by weight, the capsule wall is 15 to 18 parts of a modified urea-formaldehyde resin of silylated nanocellulose, and the capsule core is 2 to 4 parts of a bisphenol S epoxy resin diluted with an active diluent; The preparation method of the microcapsule sealing material comprises the following steps: (1) dissolving the reactive monomer urea of the capsule wall material in a formaldehyde (37% to 40%) aqueous solution, stirring under constant temperature magnetic force for 0.5 to 1 h at room temperature, and preparing a solution with ethanol and deionized water in a volume ratio of 3:1, adding hexadecyltrimethoxysilane and nanocellulose, and then transferring the mixed solution into a 250 ml three-necked flask, adjusting the temperature of a constant temperature water bath to 75° C., and continuously stirring to obtain a viscous and transparent prepolymer aqueous solution; (2) adding urea-formaldehyde resin prepolymer, compound emulsifier, bisphenol S epoxy resin and its active diluent into a 500 ml four-necked flask, adding a pH adjuster to make the mixed solution neutral, stirring it evenly with a glass rod, adding 1 to 2 drops of n-octanol as a defoaming agent, reacting in a constant temperature water bath at 60° C., with a rotation speed of 500 to 800 rpm, to obtain a stable oil-in-water (O / W) emulsion; (3) placing the mixed emulsion in step (2) in a water bath, adding a certain amount of ammonium chloride to the flask in portions, slowly adjusting the pH value of the solution to 3-4, and reacting for 1-2 hours at a certain temperature and stirring speed. At this time, the environment is acidic, and urea-formaldehyde resin particles gradually deposit on the surface of the epoxy resin droplets to form the capsule wall of the microcapsule; (4) adding an appropriate amount of curing agent to the acidified microcapsule solution, and slowly raising the temperature to 80° C. to cure the microcapsules for a period of time. When the temperature drops to room temperature, washing the reaction product 3 to 4 times with a 30% ethanol solution, and then filtering it under reduced pressure with a Buchner funnel. After filtering, drying, placing it in an electric constant temperature forced air drying oven at 65° C. for 24 hours, thereby obtaining urea-formaldehyde resin-epoxy resin microcapsules; (5) A 1% acetic acid solution is prepared as a hydrolysis catalyst, a silane coupling agent is dropped into the acetic acid solution, and the mixture is stirred rapidly to prevent the formation of gel, an appropriate amount of microcapsule powder is added to the silane coupling agent aqueous solution, and the mixture is reacted at a constant temperature of 30 to 40° C. for 1 hour, and the microcapsules are taken out and washed with deionized water for 3 to 4 times, and then filtered and dried to obtain a microcapsule sealing material sample whose surface is covered with a silane coupling agent; further, the synthesized microcapsules are incorporated into a cement-based material to obtain a self-repairing microcapsule cement-based sealing material.
2. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the urea to the formaldehyde solution is 1:1-2.
3. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (1), the mass ratio of hexadecyltrimethoxysilane to nanocellulose is 3:
1.
4. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (1), the stirring speed of the constant temperature water bath is 300-500 rpm; and the mass ratio of urea-formaldehyde resin prepolymer to epoxy resin is 1.2:
1.
5. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (2), the active diluent is 1,4-butanediol diglycidyl ether, and the amount of the active diluent is 10% to 20% of the epoxy resin.
6. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (2), the compound emulsifier is sodium dodecylbenzene sulfonate (LAS) and fatty alcohol polyoxyethylene ether (AEO-9), and the compounding ratio is 1:1, that is, the mass ratio of the two emulsifiers is 1:1; the pH regulator is a dilute hydrochloric acid solution with a concentration of 2% to 4%.
7. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (3), the stirring temperature is 60-70° C. and the stirring speed is 400-500 rpm.
8. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (4), the curing agent is a fatty amine curing agent triethylenetetramine, and the curing time is 2 hours.
9. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (5), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, namely KH-570 silane coupling agent; the mass ratio of the silane coupling agent aqueous solution to the urea-formaldehyde resin-epoxy resin microcapsules is 1:
25.
10. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (5), the drying temperature is 55°C to 65°C, and the drying time is 2 to 3 hours.
11. The mining microcapsule self-repairing sealing material and preparation method according to claim 1, characterized in that: In step (5), the amount of microcapsules added is 3% to 4% of the cement content.
Citation Information
Patent Citations
Hole sealing material for gas extraction and using method of hole sealing material
CN111911111A
Coal mine underground gas extraction hole sealing material and preparation method thereof
CN113636789A
Swelling type micro-capsule / cement-based self-repair system
CN108409178A
Waterproof repair resin material using microcapsule technology
CN114790088A
Microcapsule for magnesium alloy self-repairing anti-corrosion coating, preparation method of microcapsule and self-repairing anti-corrosion coating
CN115738938A